#### Answer

$x=7$

#### Work Step by Step

Square both sides of the equation to obtain:
$x^2=6x+7$
Move all terms on the left side of the equation. Note that when a term is moved to the other side of the equation, its sign changes to its opposite.
$x^2-6x-7=0$
Factor the trinomial to obtain:
$(x-7)(x+1) = 0$
Equate each factor to zero then solve each equation to obtain:
$x-7 = 0 \text{ or } x + 1 = 0
\\x = 7 \text{ or } x = -1$
The principal root of a square root cannot be negative. This means that $x=-1$ is an extraneous root.
Therefore, the solution is $x=7$.